Who was Wolfgang Amadeus Mozart? - McDonough, Yona Zeldis; Robbins, Carrie (New York : Grosset & Dunlap, 2003)
Explores the life and work of the prolific eighteenth-century Austrian composer who began life as a child prodigy, composing music at the age of five, and died a pauper at age thirty-five.
Includes bibliographical references (p. 106).
5.4
3-6
5.4
Keywords: Mozart, Wolfgang Amadeus, -- 1756-1791 -- Juvenile literature; Mozart, Wolfgang Amadeus, -- 1756-1791.; Mozart, Wolfgang Amadeus, -- 1756-1791.; Composers -- Austria -- Biography -- Juvenile literature; Composers; Composers -- Biography